Development of Drum Brake Pad Material Motorcycle Based Composite Hazelnut Shells, Aluminum and Pineapple Leaf Fibers with Polyurethane Matrix - Isranuri, Ikhwansyah; Adan Silalahi, Jepri; Wirjosentono, Basuki; ., Warman (International Journal of Engineering and Technology, 2019)
The development of automotive technology from time to time is something that must be faced. Materials needed for such technology must also continue in innovation from hard-to-find materials in nature to be easy to come by, such as composite materials. So it creates a technology that is cheap and environmentally friendly. The composite materials are progressing very rapidly due to the renewable or renewable properties features as well as the high strength to weight ratio of stiffness, corrosion resistance and others, thus reducing the consumption of chemicals as well as environmental disturbances [1]. Motorcycles are the result of technological developments that require many components and types of materials. Motorcycle components are most often replaced and also important to note in order to maintain safety both by vehicle technology designers and drivers who use the vehicle is the brake system. Brake pad is one of the most important parts of the braking system [2]. The strength of the brake pad recording depends heavily on the brake pad material. Materials for brake pad sold in the market are asbestos, steel fiber, cellulose, rock wool, graphite and kevlar. From the material of the brake pad in circulation raises concerns about its dangerous particles [3]. Uses such as asbestos can cause cancer disease [4]. While the increased use of other materials are leading to scarcity in nature, so there is a need to find another alternative as a friction material for brake pad. To overcome this, various types of brake pad materials are developed.The strength of the brake particle composite material is greatly influenced by the particle, its matrix material and the manufacturing process. The particle composite strength is obtained maximally in sizes from 0.01 to 0.1 mm and the strength of surface bonding, diffusion, and sintering [5].Currently, there are three universally accepted friction material formulations for brake pad [6] (1) semi metallic, Semi metallic brake pad is made of steel fiber as fiber reinforcement. Most semi-metallic friction materials contain at least 60% steel fiber. Steel fiber acts as a frame work to bind the friction material simultaneously. (2) Organic non-asbestos (NAO), an organic Non-asbestos brake pad (NAO) consists of organic fibers used to strengthen the friction materials and provide strength to the brake pad. The NAO friction materials contains less than 20% heavy steel fibers, the NAO brake pads are designed to replace the dangerous asbestos brake pad and are popular in pre-FWD vehicles. (3) Ceramic, ceramic brake lining does not contain steel fiber. Instead, this formulation uses ceramic and copper fibers to manage heat dissipation.The technical requirements of brake pad are in accordance with SAE J661 standard [1] (1) Hardness value according to security standard 68-105 (Rockwell) (2) Heat resistance 360 0C, for continuous use up to 250 0C (3) Value brake pad wear is 5x10-4 - 5x10-3 mm2.kg-1 (4) Brake pad mass is 1.5-2.4 gr.cm-3 and fracture strength 480-1500 N.cm-2.